Cytokines in the seronegative spondyloarthropathies and their modification by TNF blockade: a brief report and literature review. Issue 12 (21st November 2003) - Keller, C; Webb, A; Davis, J
Abstract : Rheumatoid arthritis (RA) is a disease well characterised by proinflammatory cytokine secretion (particularly tumour necrosis factor, interferon gamma, interleukin (IL) 1, and IL6). Less has been reported about the cytokine profiling in the spondyloarthropathies (SpA). Several trials suggest that, similar to RA, proinflammatory cytokines are globally expressed in the SpA. However, other studies report a down regulation of these cytokines in the SpA, with a relative anti-inflammatory polarisation (featuring increases in IL4, IL5, and IL10). This review summarises current published reports and the variation in cytokine data in the SpA. Additionally, results of cytokine profiles in patients with ankylosing spondylitis before and after treatment with etanercept are reported.